A genetic approach to the selection of the variable structurecontroller feedback gains - Al-Duwaish, H.N. (1998)
A method of determining the variable structure controller switching vector gains is presented. Contrary to the trial and error selection of the variable structure feedback gains reported in the literature, the selection in the present work is done using genetic algorithms. The proposed design has been applied to the load frequency problem of a single area power system. The system performance against step load variations has been simulated and compared to some previous methods. Simulation results show that the dynamic system performance has been improved